Adsorption of Crystal Violet oNto Nitrogen-Doped Mesoporous Carbon. (September 2017) - Zhong, Lvling; Zhang, Liang; Shi, Hongliang
A series of nitrogen-doped mesoporous carbons (NDMCs) was prepared using p -phenylenediamine and glyoxal as a carbon source and mesoporous silica as a hard template. N2 adsorption–desorption isotherms indicated that mesopores with a wider distribution exist in NDMCs. Elemental analysis showed that the N content on the surface of NDMC-800 was 9.9at.%, with a result close to 8.4at.% from X-ray photoelectron spectroscopy. The adsorption capacity of NDMCs for crystal violet (CV) in aqueous solution was investigated. Static equilibrium data were well described by the Langmuir isotherm model, with a maximum adsorption capacity of 243.9 mg g −1 . Adsorption kinetics data suggested that the adsorption control process follows the pseudo first-order kinetics model. The results showed that this carbon material has the potential for application in adsorption of CV.